Imperial sequential art: internal and foreign policy in the pages of Il Giornale del Balilla - Elia, Domenico Francesco Antonio (Rivista di Storia dell’Educazione, 2025)
This paper examines the relationship between sequential art and fascist propaganda, drawing on scientific literature that for the last twenty years has investigated graphic fiction and the periodicals where it was published. It analyses the weekly magazine Il Giornale del Balilla, published from 1923 onwards: its pages featured a series of self-contained “picture stories” focusing on the war in Ethiopia (1935-1936), many of which were the work of Enrico De Seta, considered one of the greatest illustrators of the 1930s in Italy. The aim is to investigate the link between the imperialist and racist propaganda promoted by the sequential art published in Il Giornale del Balilla, formal education and the iconographic production typical of contemporary mass education media, such as the covers of notebooks. The “picture stories”, framed within this comparative analysis, proved to be ideological vehicles that played a fundamental role in the education of the younger generations according to the value system of the fascist “New Man”.